Real wages and the origins of modern economic growth in Germany, 16th to 19th centuries - Martin Uebele; Ulrich Pfister; Jana Riedel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
The study develops two new real wages series for Germany c. 1500-1850 and analyzes their relationship with population size. From 1690 data density allows the estimation of a structural time series model of this relationship. The major results are the following: First, there was a strong negative relationship between population and the real wage until the middle of the seventeenth century. The dramatic rise of material welfare during the Thirty Years War was thus entirely due to the war-related population loss. Second, the relationship between the real wage and population size was much weaker in the eighteenth than in the sixteenth century; the fall of the marginal product of labor was less pronounced, and the beginning of the eighteenth century saw a marked increase of labour demand. Third, labor productivity underwent a strong positive shock during the late 1810s and early 1820s, and continued to rise at a weaker pace during the following decades. This growth was only temporarily interrupted by negative shocks uring the late 1840s and early 1850s. Results two and three suggest the onset of sustained economic growth well before the beginnings of industrialization, which set in during the third quarter of the nineteenth century.
Keywords: C32; J20; N13; 330